Combination versus single-agent as palliative chemotherapy for gastric cancer - Choi, Jin-Hyuk (BMC Cancer, 2020)
BACKGROUND: Although combination chemotherapy (CC) is generally recommended in recurrent or primary metastatic gastric cancer (RPMGC), the results of randomized trials are conflicting. METHODS: A retrospective review was conducted on 687 RPMGC patients who received palliative chemotherapy. We compared the overall survival (OS) between CC and single-agent chemotherapy (SC) among these patients, and we analyzed the clinicopathological characteristics affecting outcome including neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR). RESULTS: Although 521 patients (75.8%) underwent CC, SC was more frequently performed in elderly patients (57.6%) and ECOG performance status (PS) 2 or 3 (65.8%) patients (p < 0.0001, in each case). The median OS of patients who received CC was significantly longer than that of patients who received SC (11 vs. 8 months, p < 0.0001). No difference in OS between CC and SC was observed in elderly patients (p = 0.583), poor PS (p = 0.810), signet ring cell (p = 0.347), palliative surgical resection (p = 0.307), and high PLR (p = 0.120), with a significant interaction between age and type of regimen (p = 0.012). Moreover, there was no difference in OS between CC and SC after propensity score matching (p = 0.322). Multivariate analysis revealed that palliative resection and ≥ second-line chemotherapy were independently associated with favorable OS (p < 0.0001, in each case), whereas poor PS (p = 0.004), signet ring cell (p < 0.0001), peritoneal metastasis (p = 0.04), high NLR (p = 0.001), and high PLR (p = 0.033) were independent prognostic factors of poor OS. CONCLUSIONS: Although CC is the standard of care in RPMGC, SC can be considered a reasonable option in certain subgroups, such as elderly patients.